2020
DOI: 10.1002/anr3.12048
|View full text |Cite
|
Sign up to set email alerts
|

Failure of standard tracheostomy decannulation criteria to detect suprastomal pathology

Abstract: Meeting established criteria for tracheostomy decannulation should improve success, although there will be a small proportion of patients with a tracheostomy who fail decannulation. Failure rates depend on patient characteristics and disparity between institutional practices and expert opinion. However, there are no widely accepted published failure rates, or agreement on the time-point at which failure is assessed. We present a patient who had evidence of readiness for decannulation, but had immediate failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Moreover, performing the retrograde and antegrade tracheoscopy after removing the tube could also aid in unmasking the underlying tracheomalacia, which can be observed in many patients with long-standing tracheostomy dependence. 1 The assessment of the airway by flexible tracheoscopy is dependent on the observer. 19 In the present study, although eight consultant otolaryngologists were involved in the airway assessment, an evaluation of the interobserver variability was not possible due to the retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, performing the retrograde and antegrade tracheoscopy after removing the tube could also aid in unmasking the underlying tracheomalacia, which can be observed in many patients with long-standing tracheostomy dependence. 1 The assessment of the airway by flexible tracheoscopy is dependent on the observer. 19 In the present study, although eight consultant otolaryngologists were involved in the airway assessment, an evaluation of the interobserver variability was not possible due to the retrospective nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the procedure itself may sound simple, the implications of improperly-performed and abrupt decannulation can be catastrophic at times. 1,2 To be eligible for decannulation, a patient with a tracheostomy should have a reasonable neurological status, with a good swallowing function, an adequate airway, and a satisfactory pulmonary function. [3][4][5][6] To elaborate, as for the neurological status, the patient should be conscious and alert, and have a good cough reflex to clear the secretions from the lower airway.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study including 50 patients demonstrated a similar rate [ 11 ]. The wide variation in failure rates may be due to a lack of agreement on the time-point for assessing failure [ 23 ]. A previous study reported failure rates between 3.5% and 32% with registration of recannulation within 1-60 days [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These inspiratory negative pressures may be sufficient to overcome the structural integrity of incompetent or narrowed supra-stomal segments due to the collapsing pressures generated. Inability to tolerate capping may be indicative of laryngotracheal pathology although the tracheostomy tube itself may "splint" the suprastomal tracheal segment during these negative pressure swings and mask potential complications [4]. While "capping" is discussed in the literature, the purpose, timing and duration of applying a tracheostomy cap lacks consensus and guidelines.…”
Section: Laryngotracheal Stenosismentioning
confidence: 99%
“…
These criteria can be insufficient to detect the presence of suprastomal pathology as described previously [4], although this complication occurs infrequently compared to the number of patients who can be successfully decannulated using recognized decannulation criteria [5]. This narrative explores the rationale underlying the components
…”
mentioning
confidence: 99%